2005
DOI: 10.2527/2005.833722x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary crude protein concentration and source on potential ammonia emissions from beef cattle manure1,2,3

Abstract: Emissions of ammonia, as well as other gases and particulates, to the atmosphere are a growing concern of livestock producers, the general public, and regulators. The concentration and ruminal degradability of CP in beef cattle diets may affect urinary and fecal excretion of N and thus may affect ammonia emissions from beef cattle feed yards. To determine the effects of dietary CP concentration and degradability on potential ammonia emissions, 54 steers were randomly assigned to nine dietary treatments in a 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 25 publications
6
58
1
Order By: Relevance
“…In our study, only a relatively small proportion of urinary N applied to the system was lost as ammonia N (2.4 to 8.1%) over 11 d. These values are similar to those of Cole et al (2005) who reported between 3.15 and 4.34% of applied urinary N being lost as ammonia from the same chambers under very similar conditions and length of analyses. This may be in part due to the low rate of turnover of gas within the chambers (1.2 turnovers/min).…”
supporting
confidence: 78%
See 3 more Smart Citations
“…In our study, only a relatively small proportion of urinary N applied to the system was lost as ammonia N (2.4 to 8.1%) over 11 d. These values are similar to those of Cole et al (2005) who reported between 3.15 and 4.34% of applied urinary N being lost as ammonia from the same chambers under very similar conditions and length of analyses. This may be in part due to the low rate of turnover of gas within the chambers (1.2 turnovers/min).…”
supporting
confidence: 78%
“…The in vitro ammonia emission system has been described previously (Shi et al, 2001;Cole et al, 2005). Briefly, the system was composed of 48 sealed polyethylene chambers (20 cm × 20 cm × 12 cm), each attached to 2 ammonia-trapping bottles containing 100 mL of 0.9 M sulfuric acid at room temperature (∼24°C).…”
Section: In Vitro Ammonia Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it makes sense that as carbohydrates in manure are initially consumed for respiration the overall manure C concentration would go up. This would be exacerbated by the loss of other volatiles with even lower C contents, such as urea, ammonia, and fermentation products all of which have been reported in cattle manure (Miller and Varel 2002;Cole et al 2005;Pratt et al 2014). Later during decay, as more complex C compounds are consumed in biological processes and the ash content increases relative to the volatile content, manure C concentrations would drop, which was observed in our work.…”
Section: Resultssupporting
confidence: 51%